Grassroots Energy Emancipation through Solar Energy Projects: Narratives from Jayuya, Puerto Rico. - RIVERA MATOS, YÍAMAR (Centro Journal)
In modern societies, our political and economic orders and daily life experiences are organized around complex socio-technical systems. These complex systems—which form societies’ dominant regimes—are colonial, extractive, and cause harm to communities that have been oppressed and that are on the frontlines and vulnerable. The oppression, vulnerabilities, and exclusion of the system design provokes a need for emancipation: the idea of reconfiguring socio-technical arrangements to empower and enable possibilities for sovereignty for these communities. To illustrate what emancipation looks like, from the perspective of subjugated communities, I develop in this article a case study of the Puerto Rico energy system. Specifically, I explore the case of the Veguita Zama community in Jayuya, where the community is building a subaltern reality of Puerto Rico’s energy transition in which the people are the protagonists. Since its construction in the mid-20th century, Puerto Rico’s current energy system has not equally served its residents, putting vulnerable communities at risk, specifically in the southern coast and central mountain regions. Events like Hurricanes Irma and María in 2017 significantly worsened the condition of the energy system, leaving many communities in a nine-month blackout and, subsequent to restoration of service, more vulnerable to frequent outages, including from recent earthquakes. In response to the socio-technical system’s oppression, local communities have been exploring solar energy as an alternative for survival. I used semi-structured interviews and participatory observation to document the new, community-centered energy narratives about creating an emancipatory energy project. The subaltern case is a history of the present, composed of stories from the people working towards social change and a sustainable future through solar energy technologies. This article aims to describe and theorize the community’s energy planning and contribute to their common well-being and commonwealth. This study could serve as an example to develop possible energy future scenarios for Puerto Rico and other island states worldwide that are also adapting to and mitigating climate change.